2017
DOI: 10.1002/term.2428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the new Japanese legislation for expedited approval of regenerative medicine products with the existing systems in the USA and European Union

Abstract: Legislation for expedited‐approval pathways and programmes for drugs, biologics or medical devices has been enacted for rapid commercialization of innovative products in the United States of America (USA) and the European Union (EU). However, less innovative products are increasingly benefitting from these expedited‐approval pathways, and obligations to collect and report post‐marketing data on approved products are being bypassed frequently. The Japanese government recently enacted legislation for a new condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Under the Japanese Pharmaceuticals and Medical Devices Act, regenerative medicine products are those that consist of processed human/animal cells that are designed to be used for reconstructing, repairing, or substituting human tissues or organs, or for treating or preventing human diseases. Products that contain modified cells with recombinant nucleic acids that are intended to be used for the treatment of human diseases are also considered regenerative medicine products [ 21 , 22 ].…”
Section: Atmp Regulatory Frameworkmentioning
confidence: 99%
“…Under the Japanese Pharmaceuticals and Medical Devices Act, regenerative medicine products are those that consist of processed human/animal cells that are designed to be used for reconstructing, repairing, or substituting human tissues or organs, or for treating or preventing human diseases. Products that contain modified cells with recombinant nucleic acids that are intended to be used for the treatment of human diseases are also considered regenerative medicine products [ 21 , 22 ].…”
Section: Atmp Regulatory Frameworkmentioning
confidence: 99%
“…27 Each approval process aims at giving patients better access to innovative drugs and regenerative medicine products. 28,29 These regulatory pathways are relatively new, and changes will likely be needed to produce safe cell therapy products that are effective. Through clinical experiences, several hurdles have been identified.…”
Section: T a G G E D H 1 What Are The Hurdles To Overcome?t A G G E Dmentioning
confidence: 99%
“…It is suggested that conditional approval in Japan could facilitate early access for patients in need while protecting public health to a larger extent than expedited regulatory pathways in other jurisdictions . However, the extent of risks and uncertainties upon conditional approval in Japan are likely to be of a larger magnitude compared to expedited regulatory pathways elsewhere, which could also endanger public health regardless of risk management strategies.…”
Section: Consequences and Potential Implicationsmentioning
confidence: 99%